Breve discusión de la economía política de los flujos financieros ilícitos en el mundo y América Latina - King, Katiuska (2018)
The present article analyzes if the problem of the illicit financial flows can be explained from a global or regional perspective, identifying points of agreement and disagreement among the interests of the countries depending on the effects that it generates, as well as of the current proposals of solution. The social dumping and the financial stability are told in the principal elements of agreement whereas the financial recycling and the institutions that discuss the solutions are key components of disagreement.